Kuesioner Pengkajian Spiritual Pada Pasien Kanker Payudara: Literatur Review - Harisandy, Alvian; Putri, Anggy Utama; Arsi, Ranida; Saputra, Andre Utama; N, Nurmalasari (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Measurement of spiritual outcome criteria is fundamental in both clinical practice and research. Measuring instruments for measuring outcome criteria are used to screen for spiritual distress. The purpose of this literature review is to find out what questionnaires can be used for spiritual assessment in breast cancer patients. The method used is a literature review through the Google Scholar, Proquest, Science direct, Pubmed and ClinicalKey databases. The results of the study showed that there were 5 spiritual assessment questionnaires, namely the FACIT-Sp Instrument (Functional Assessment of Chronic Illness Therapy-Spiritual), Instrument Spiritual Well-Being Scale (SWBS), FICA Instrument (Faith, Influence, Community, and Addressing spiritual concerns), Instrument Spiritual Needs Questionnaire (SpNQ), Instrument Spirituality and Spiritual Care Rating Scale (SSCRS). The conclusion is that more articles are needed on spiritual questionnaires, especially in breast cancer so that the questionnaire can be used in practice, especially in the area of oncology nursing services for breast cancer patients.